ТӘЛИМ-ТӘРБИЯ ПРОЦЕСИН ШӨЛКЕМЛЕСТИРИЎДЕ ОҚЫЎШЫЛАРДЫҢ ТЕМПЕРАМЕНТЛЕРИН ЕСАПҚА АЛЫЎ МӘСЕЛЕЛЕЛЕРИ - Палўанова, Г.Ж.; Марасулова, Д. (FAN va JAMIYAT, 2018)
The article is devoted to the study and description of the physiological and psychological traits of children with different temperament (choleric, sanguine, phlegmatic, melancholic) in the educational process.